2019
DOI: 10.1111/cup.13608
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic aggregates with unique morphology associated with regression of basal cell carcinoma

Abstract: Background: Spontaneous regression of basal cell carcinomas (BCC) is a welldocumented phenomenon. In practice, we have observed melanocytic aggregates associated with BCC at various stages of regression showing unique morphologic features.Methods: Fourteen cases featuring melanocytic aggregates were retrospectively identified through a pathology database search. Clinical and histopathologic features were systematically evaluated, and additional immunohistochemical studies were performed. Melanocyte density wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Pseudomelanocytic nests have been described in various interface processes, including lichen planus, 5 lichen planus pigmentosus, 2,4 lupus erythematosus, 6,7 fixed drug eruption, 3 and phototoxic reactions 2 . This phenomenon has also been described in solitary lesions such as pigmented lichenoid keratosis 2 and basal cell carcinoma with regression 8 . Given that 6.7% of melanomas are associated with a lichenoid tissue reaction, 9 pseudomelanocytic nests can be a potential diagnostic pitfall for inflamed or regressed melanoma in situ (MIS).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pseudomelanocytic nests have been described in various interface processes, including lichen planus, 5 lichen planus pigmentosus, 2,4 lupus erythematosus, 6,7 fixed drug eruption, 3 and phototoxic reactions 2 . This phenomenon has also been described in solitary lesions such as pigmented lichenoid keratosis 2 and basal cell carcinoma with regression 8 . Given that 6.7% of melanomas are associated with a lichenoid tissue reaction, 9 pseudomelanocytic nests can be a potential diagnostic pitfall for inflamed or regressed melanoma in situ (MIS).…”
Section: Introductionmentioning
confidence: 98%
“…2 This phenomenon has also been described in solitary lesions such as pigmented lichenoid keratosis 2 and basal cell carcinoma with regression. 8 Given that 6.7% of melanomas are associated with a lichenoid tissue reaction, 9 pseudomelanocytic nests can be a potential diagnostic pitfall for inflamed or regressed melanoma in situ (MIS).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies demonstrated that melanocytes in pBCCs do not have any distinct configuration and theydo not organize in clusters, a feature that is more likely to be seen in melanoma 27,31. Jackson et al32 in a case series of 14 spontaneously regressed BCC identified melanocytic aggregates associated with BCC at different stages of regression. They speculated that in BCC's regression, mostly in pBCCs, the immune response may target the basal cells and spare the melanocytes, allowing them to organize in nest like structures or as scattered solitary melanocytes.…”
mentioning
confidence: 99%